An Overview on Supply Chain Vulnerability and Resilience - Jain, Jinesh Kumar (International Journal of Scientific Research and Management (IJSRM), 2013)
In this age of complexity of markets, uncertainty, and turbulence, supply chain has become vulnerable to different kinds of risks. As supply chains increase in complexity due to outsourcing, globalization and volatility in environment, the risk of disturbances may increase and variability is beyond a company’s control. Being so, companies need to adopt disturbance-management practices at strategic, tactical and operational levels. Further globalization and recession has leaned the supply chain, causes more risks. The concentration of organizations is to minimize the risk; through designing a more resilient supply chain. Here different requisites of resilient supply chain are discussed, to mitigate the supply chain risks.